Response to different medical treatment options for mastalgia in fibrocystic breast disease (BIRDEM Medical Journal, 2021)
Background: Fibrocystic breast disease is the most common type of benign breast disease and mastalgia is the most common symptom of fibrocystic breast disease. Various types of medical management are given as a gold standard treatment for that. The aim of this study was to compare the effects of different commonly used medical management options of mastalgia of fibrocystic breast disease on the quality of life of patients and their side effects as well.Methods: This quasi-experimental study was carried out in Out-patients Department of General Surgery, BIRDEM General Hospital, Dhaka, from July 2018 to June 2019. Total 45 patients with fibrocystic breast disease were selected according to the eligibility criteria and were allocated to two groups by alternative random selection. In non-pharmacological treatments receiving group, lifestyle modification advices along with evening primrose oil were given. On the other hand, in pharmacological treatment receiving group, bromocriptine and danazole were given according to some selection criteria of the patients. Response of treatments to each group and side effects were determined at one month, three months and six months follow-up respectively. Mastalgia was measured by visual analogue scale (VAS) score and quality of life was calculated by modified WHO-QOL scoring in each follow-up.Results: Patients had an average age of 30.24±6.93 years with a majority in the age group 31-35 years (33.3%). Most patients were married (64.4%), housewives (62.20%), from middle-class groups (62.20%), multiparous (57.78%) and the majority had absence of the family history of breast diseases (84.45%). Majority of them presented with cyclical mastalgia (57.78%), bilateral mastalgia (60%) and mastalgia with lumpiness (44.4%). Among the patients who received non-pharmacological treatment, mastalgia improved in 34.78% cases and patients received pharmacological treatment, mastalgia improved in 72.73% cases. Different domains of quality of life were improved significantly in patients who received pharmacological treatment. Though majority of the patients had side effects due to pharmacological treatment, they were well tolerated.Conclusion: Despite having various side effects, pharmacological management by danazol or bromocriptine was well tolerated to our patients and a dramatic improvement was observed on quality of life than the nonpharmacologically treated patients.BIRDEM Med J 2022; 12(1): 22-29